Radiotherapy Advances in Paediatric Medulloblastoma Treatment. Issue 3 (March 2019) - Padovani, L.; Horan, G.; Ajithkumar, T.
Abstract: Radiotherapy is an essential element in the multidisciplinary management of children with medulloblastoma and postoperative craniospinal axis radiotherapy is considered to be the cornerstone of curative treatment. With modern multidisciplinary management, more than 80% of children with standard-risk medulloblastoma and up to 70% of children with high-risk medulloblastoma are long-term survivors. Current clinical trials are evaluating risk-adapted radiotherapy in standard-risk medulloblastoma to reduce long-term sequelae, whereas the research approach in high-risk medulloblastoma is to improve clinical outcome with dose-intensification of chemotherapy and the use of hyperfractionated radiotherapy regimens. Technological advances, such as tomotherapy, volumetric modulated arc therapy and proton therapy, may further improve the therapeutic ratio by reducing radiotherapy toxicities. A selected group of children with recurrent disease after treatment for standard-risk medulloblastoma may be considered for re-irradiation.